Morphological evolution in the ant reproductive caste. (22nd September 2020) - Divieso, Raquel; Silva, Thiago S R; Pie, Marcio R
Abstract: The evolution of eusociality has led to considerable changes in the general hymenopteran body plan. In particular, the evolution of reproductive division of labour caused the worker caste to be largely freed from the demands involved in reproduction. As a consequence, workers were able to evolve highly specialized morphologies for foraging and colony maintenance, whereas the reproductive caste became specialized for reproduction. Despite these important changes, little is known about the general patterns of morphological evolution within the ant reproductive caste. Our goals here were to characterize morphological variation in the ant reproductive caste and to test whether different sexes display variation in their evolutionary rates. We obtained measurements of 897 specimens from a total of 678 ant species. The shapes of the size distributions were similar between sexes, with queens being larger than males in all traits except for eye length. Contrary to the expectation based on Rensch's rule, although queens were larger, the degree of dimorphism increased with body size. Finally, there was strong evidence for an accelerated tempo of morphological evolution in queens in relation to males. These results represent the first comprehensive treatment of morphological variation in the ant reproductive caste and provide important new insights into their evolution.